Characteristics of long-term home oxygen therapy users in the municipality of Curitiba, Brazil - Demetria Kovelis; Paôla Luma Cruz; Lígia Inez Silva; Juan Ricardo Sierra; Paulo Roberto de Miranda Sandoval; Silvia Valderramas (Editora Champagnat, 2019)
Abstract Introduction: Long-term home oxygen therapy (LTOT) can be successfully used in the treatment and prevention of chronic lung diseases, as it improves quality of life, increases survival, and reduces the lenght of hospital stays. However, to the authors' knowledge there are no descriptive studies with details of the clinical and social profile of patients using LTOT in the state of Paraná. Objective: To analyze the profile of LTOT users in the state of Paraná. Method: All patients registered in the LTOT program of the Curitiba Municipal Department of Health were recruited to the study. Participants answered a questionnaire with questions about their education level, family income, main diagnosis, comorbidities, hours/day of O2 use, and hospitalizations in the previous year. Results: 386 patients (67 ± 20.4 years; 66% females) were interviewed. Chronic obstructive pulmonary disease (COPD) was the most common disease (58.5%); 60.6% were former smokers and 84.5% did not practice any kind of physical activity; dyspnea was the most common symptom (81.3%) and immobility was the most commonly reported inconvenience (33%); 55.7% used O2 24 hours a day; 53.6% had been hospitalized in the previous year; 33.9% had not completed primary school; 31.4% had an income of one minimum monthly wage or less. Conclusion: LTOT users in Curitiba are primarily elderly women with COPD, with low family income and limited schooling. It is extremely important that health professionals provide educational and preventive measures for this population, to minimize the impact of COPD in the community.